CHEMICAL VALORISATION OF CARBON DIOXIDE ([S.l.] : ROYAL SOCIETY OF CHEMISTR, 2022)
Providing a comprehensive panorama of advances in the technologies for chemical valorisation of carbon dioxide, this book is essential reading for anyone with an interest in sustainability.
eBooks on EBSCOhost
Keywords: Carbon dioxide -- Recycling; Carbon dioxide mitigation -- Technological innovations; Green chemistry; Gaz carbonique -- Recyclage; Gaz carbonique -- Réduction -- Innovations; Chimie verte; Industrial & Technical; Sustainable Development; Development; BUSINESS & ECONOMICS; Environmental; TECHNOLOGY & ENGINEERING; Chemistry; SCIENCE; Carbon dioxide -- Recycling; Green chemistry